Automorphisms of homogeneous symmetric groups and hierarchomorphisms of rooted trees - Lavrenyuk, Y.V.; Sushchansky, V.I. (Algebra and Discrete Mathematics, 2003)
A representation of homogeneous symmetric
groups by hierarchomorphisms of spherically homogeneous rooted
trees are considered. We show that every automorphism of a homogeneous symmetric (alternating) group is locally inner and that
the group of all automorphisms contains Cartesian products of arbitrary finite symmetric groups.
The structure of orbits on the boundary of the tree where investigated for the homogeneous symmetric group and for its automorphism group. The automorphism group acts highly transitive on
the boundary, and the homogeneous symmetric group acts faithfully on every its orbit. All orbits are dense, the actions of the
group on different orbits are isomorphic as permutation groups.